Protein modifications in hepatic ischemia-reperfusion injury: molecular mechanisms and targeted therapy - Zhao, Xiaohong; Li, Qinyi; Zhu, Xiaolong; Jiao, Yuanyuan; Yang, Huan; Feng, Jiao (Frontiers in Immunology, 2025)
Ischemia-reperfusion injury refers to the damage that occurs when blood supply is restored to organs or tissues after a period of ischemia. This phenomenon is commonly observed in clinical contexts such as organ transplantation and cardiac arrest resuscitation. Among these, hepatic ischemia-reperfusion injury is a prevalent complication in liver transplantation, significantly impacting the functional recovery of the transplanted liver and potentially leading to primary graft dysfunction. With the growing demand for organ transplants and the limited availability of donor organs, effectively addressing hepatic ischemia-reperfusion injury is essential for enhancing transplantation success rates, minimizing complications, and improving graft survival. The pathogenesis of hepatic ischemia-reperfusion injury is multifaceted, involving factors such as oxidative stress and inflammatory responses. This article focuses on the role of protein post-translational modifications in hepatic ischemia-reperfusion injury, including phosphorylation, ubiquitination, acetylation, ADP-ribosylation, SUMOylation, crotonylation, palmitoylation, and S-nitrosylation. Initially, we examined the historical discovery of these protein post-translational modifications and subsequently investigated their impact on cellular signal transduction, enzymatic activity, protein stability, and protein-protein interactions. The emphasis of this study is on the pivotal role of protein post-translational modifications in the progression of hepatic ischemia-reperfusion injury and their potential as therapeutic targets. This study aims to conduct a comprehensive analysis of recent advancements in research on protein modifications in hepatic ischemia-reperfusion injury, investigate the underlying molecular mechanisms, and explore future research trajectories. Additionally, future research directions are proposed, including the exploration of interactions between various protein modifications, the identification of specific modification sites, and the development of drugs targeting these modifications. These efforts aim to deepen our understanding of protein post-translational modifications in hepatic ischemia-reperfusion injury and pave the way for innovative therapeutic interventions.